2004
DOI: 10.1111/j.1523-1755.2004.00479.x
|View full text |Cite
|
Sign up to set email alerts
|

NPHS2 R229Q functional variant is associated with microalbuminuria in the general population

Abstract: These data have important implications for the understanding of microalbuminuria in the general population and may contribute to better ways of disease prediction and prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
78
1
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(88 citation statements)
references
References 14 publications
4
78
1
5
Order By: Relevance
“…Furthermore, our results are in agreement with a previous report excluding linkage to diabetic ESRD for the NPHS2 and ACTN4 loci in White and African-American populations [8]. The only functional polymorphism studied here, R229Q in the NPHS2 gene, has been suggested to contribute to susceptibility to microalbuminuria in the general population [9]. However, we could not establish such a relationship between AER and the R229Q variant, or any other variant in the NPHS2 gene, in patients with type 1 diabetes.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, our results are in agreement with a previous report excluding linkage to diabetic ESRD for the NPHS2 and ACTN4 loci in White and African-American populations [8]. The only functional polymorphism studied here, R229Q in the NPHS2 gene, has been suggested to contribute to susceptibility to microalbuminuria in the general population [9]. However, we could not establish such a relationship between AER and the R229Q variant, or any other variant in the NPHS2 gene, in patients with type 1 diabetes.…”
Section: Discussionsupporting
confidence: 93%
“…This variant has a frequency of 4% in the general Cypriot population. It is worth mentioning that, although an earlier report had associated R229Q with microalbuminuria in the Brazilian population, a more recent work with larger numbers did not corroborate those data in a US adult population [13,14].…”
mentioning
confidence: 66%
“…Its relevance is controversially discussed. In vitro studies demonstrated a reduced binding capacity to nephrin for R229Q-podocin (31), and some studies point to an association of R229Q and development of microalbuminuria in the general population (32) or an enhanced allele frequency of R229Q in nongenetic FSGS patients (31,33). Machuca et al reported a large number of FSGS patients heterozygous for R229Q in association with a second pathogenic mutation in NPHS2; these patients typically present with later onset of disease and slower progression to ESRD (34).…”
Section: Discussionmentioning
confidence: 99%